2011
DOI: 10.1371/journal.pmed.1001046
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Health and Return Migration

Abstract: In the final article in a six-part PLoS Medicine; series on Migration & Health, Anita Davies and colleagues from the International Organization for Migration (IOM) discuss the specific health risks and policy needs associated with return migration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(97 citation statements)
references
References 10 publications
6
91
0
Order By: Relevance
“…Return migrants’ health is an under-researched issue, determined by a ‘cumulative exposure’ to risks and behaviour during the entire migration process; that is, by conditions and events before, during and after the actual migration [98]. The findings in this study confirm this, in that the circumstances surrounding migration events seemed highly influential in how the return was experienced by the migrant, and in the consequences on health.…”
Section: Resultssupporting
confidence: 74%
“…Return migrants’ health is an under-researched issue, determined by a ‘cumulative exposure’ to risks and behaviour during the entire migration process; that is, by conditions and events before, during and after the actual migration [98]. The findings in this study confirm this, in that the circumstances surrounding migration events seemed highly influential in how the return was experienced by the migrant, and in the consequences on health.…”
Section: Resultssupporting
confidence: 74%
“…Costs associated with unexpected medical procedures disrupt families' socioeconomic strategies by diverting resources away from investments such as children's education or the formation of a businesses (Galárraga et al, 2010; Knaul & Frenk, 2005), important mobility strategies among less educated Mexicans. Moreover, among return migrants, health costs can motivate future migrations, disrupting returnees' settlement plans and potential investments in their origin communities (Davies, Borland, Blake, & West, 2011; Hagan & Wassink, 2016). Formal mediation analysis revealed that more than half of the association between migration experience and access to care was explained by migrants' low levels of health insurance coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have pointed out the necessity of public health policies addressed to return migrants [28]. In the case of forced returnees, this necessity is even more pressing, as they are less likely to have prepared their return in advance [11,12].…”
Section: Discussionmentioning
confidence: 99%